2020
DOI: 10.3389/fphys.2020.00128
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochromes Mediate Intrinsic Photomechanical Transduction in Avian Iris and Somatic Striated Muscle

Abstract: Irises isolated from the eyes of diverse species constrict when exposed to light. Depending on species this intrinsic photomechanical transduction response (PMTR) requires either melanopsin or cryptochrome (CRY) photopigment proteins, generated by their respective association with retinoid or flavin adenine dinucleotide (FAD) chromophores. Although developmentally relevant circadian rhythms are also synchronized and reset by these same proteins, the cell type, mechanism, and specificity of photomechanical tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…One of the most important modification to the biological function of FANA ASO molecules is their ability to penetrate cells without the necessity of delivery vehicles required in transfection approaches. Our results revealed that FANA ASO molecules targeting CCL3 can indeed penetrate BMDMs in gymnotic fashion, as previously described for other cell types in vitro (Baby et al, 2020;Margiotta and Howard, 2020;Schmidt et al, 2019;Smaldone et al, 2019;Suwanmanee et al, 2019;Takahashi et al, 2019). We also demonstrated the successful suppression of CCL3 expression in BMDMs by CCL3 specific FANA ASOs.…”
Section: Discussionsupporting
confidence: 85%
“…One of the most important modification to the biological function of FANA ASO molecules is their ability to penetrate cells without the necessity of delivery vehicles required in transfection approaches. Our results revealed that FANA ASO molecules targeting CCL3 can indeed penetrate BMDMs in gymnotic fashion, as previously described for other cell types in vitro (Baby et al, 2020;Margiotta and Howard, 2020;Schmidt et al, 2019;Smaldone et al, 2019;Suwanmanee et al, 2019;Takahashi et al, 2019). We also demonstrated the successful suppression of CCL3 expression in BMDMs by CCL3 specific FANA ASOs.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, key components of the termite magnetic orientation system are expressed in muscle. Moreover, TRPC1 is implicated in store-operated calcium entry (SOCE) [88], and evidence of a SOCE-and flavin-dependent, redox-sensitive, photomechanical transduction process requiring the participation of Cry2 during muscle development has recently emerged [165]. Finally, the genetic knockdown of the entire TRPC family was shown to alter cryptochrome-mediated circadian ("crycadian") rhythm, cytokine, and metabolic functions [166], congruent with the cellular functions that have been correlated with TRPC1 expression.…”
Section: Proposed Mechanisms For Magnetoreceptionmentioning
confidence: 99%
“…TRPC1 has been directly implicated in phototransduction in diverse species and tissues [97][98][99]. Moreover, both magnetoreception [10] and photomechanical transduction [165] can be antagonized by the TRPC channel blocker, 2-APB, or other forms of inhibiting extracellular calcium entry, drawing provocative parallels. TRPC1 may hence comprise part of a magnetic signaling complex, analogous to Orco (olfactory sensory receptor channel) in termites [159], which in collaboration with Cry2 and potentially other molecular partners confers field directionally specific developmental responses.…”
Section: Proposed Mechanisms For Magnetoreceptionmentioning
confidence: 99%
“…As ASO design is complicated, most researchers purchase them from manufacturers. Lacking knowledge of the exact sequence or chemistry, it is much more difficult to interpret nonspecific signals and optimize design [ 129 , 130 , 131 ]. Nevertheless, there are already approaches and studies using ASOs in therapeutic contexts to treat viral diseases, genetic alterations, cancer, chronic inflammation, and COVID-19 [ 130 , 132 , 133 ].…”
Section: Nucleic Acids In Rnaimentioning
confidence: 99%